2019
DOI: 10.1002/sctm.19-0106
|View full text |Cite|
|
Sign up to set email alerts
|

Autologous cord blood cell infusion in preterm neonates safely reduces respiratory support duration and potentially preterm complications

Abstract: Preterm birth and its complications are the leading cause of neonatal death. The main underlying pathological mechanisms for preterm complications are disruption of the normal maturation processes within the target tissues, interrupted by premature birth.Cord blood, as a new and convenient source of stem cells, may provide new, promising options for preventing preterm complications. This prospective, nonrandomized placebo controlled study aimed at investigating the effect of autologous cord blood mononuclear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Yun et al 25 , Xian et al 26 and Steven et al 27 treated patients with MSCs infusions. Zhu et al 28 and Jie et al 29 administered autologous cord blood cells to infants. All the subjects in the 7 studies were premature infants with gestational ages of less than 37 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Yun et al 25 , Xian et al 26 and Steven et al 27 treated patients with MSCs infusions. Zhu et al 28 and Jie et al 29 administered autologous cord blood cells to infants. All the subjects in the 7 studies were premature infants with gestational ages of less than 37 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Because none of the children with IUGR suffered from brain lesions, we suggest that this group may be excluded for a more efficient approach in the future. Other neonatological populations that may benefit from autologous cord blood are preterm infants developing bronchopulmonary dysplasia or neonates undergoing surgical correction of congenital cardiac defects 47 , 56 59 .…”
Section: Discussionmentioning
confidence: 99%
“…As inflammation and cellular degeneration play a major role in pathological cascade of WMI, UCBCs with established immunomodulatory, anti-apoptotic, and neurotrophic properties are a promising autologous cell source for WMI cell therapy. Indeed, a number of preclinical and clinical studies have demonstrated that UCBC administration protects white matter development via prevention of OLs loss, restoration of pmOLs maturation, and exhibition of anti-inflammatory and antioxidant functions ( Li et al, 2016 ; Paton et al, 2018 ; Ren et al, 2020 ). To date, more than 20 clinical trials for CP treatment using UCB have been registered from clinicaltrials.gov ( Table 2 ).…”
Section: Enhancing Oligodendrocytes Myelination As Therapeutic Strategies Against White Matter Injurymentioning
confidence: 99%